Change Direction: Influencing the National Church through the Vatican during the Pinochet Dictatorship in Chile (2020)
The relations between the Chilean Church and the dictatorship of Augusto Pinochet (1973-1990) are often characterized as conflictive. After a short period of accommodation and legitimation, the Chilean episcopate started to confront the dictatorship in the name of the poor and persecuted, but never breaking entirely with the regime. This led to a complicated relationship between the Church and the dictatorship, which tried to legitimize authoritarian rule by reference to Christian values and the defense of "Christian civilization". Much historiography has examined this relation from the point of view of the Church. When examined from the point of view of the State important nuances appear. Documents from the Chilean Ministry of Foreign Relations and correspondence with the Chilean ambassador to the Vatican, shed new light on efforts by the Chilean state to shape relations with the Church and to change the position of bishops who were critical of the regime. These data help understand better the dynamics of conflict between Church and State in Chile during the dictatorship.